A multi-lateral trading model for coupled gas-heat-power energy networks. (15th August 2017) - Chen, Yue; Wei, Wei; Liu, Feng; Mei, Shengwei
Highlights: Optimal energy flows in the gas, heat, and power systems are modeled in detail. A multi-lateral trading model for the coupled energy markets is proposed. A two-phase algorithm for computing the market equilibrium. Case studies demonstrate that market competition pilots reasonable energy prices. Abstract: The proliferation of cogeneration technology and the need for more resilient energy utilization inspire the emerging trend of integration of multi-resource energy systems, in which natural gas, heat, and electricity are produced, delivered, converted, and distributed more efficiently and flexibly. The increasing interactions and interdependencies across heterogenous physical networks impose remarkable challenges on the operation and market organization. This paper envisions the market trading scheme in the network-coupled natural gas system, district heating system, and power system. Based on the physical energy flow models of each system and their interdependency, a multi-lateral trading gas-heat-power (MLT-GHP) model is suggested, and a mixed-integer linear programming based two-phase algorithm is developed to find the market equilibrium. Case studies on two testing systems demonstrate the effectiveness of the proposed model and method, showing that the multi-lateral trading essentially results in market competition that orientates reasonable energy prices. Some prospects for future researches are also summarized.